Hierarchical sulfonated graphene oxide–TiO2 composites for highly efficient hydrogen production with a wide pH range - Gao, Peng (2014)
Synthesizing highly efficient photocatalyst for hydrogen production still remains a great challenge, especially generating hydrogen from water with a wide pH range. In this work, for the first time, the hierarchical sulfonated graphene oxide (SG)–TiO2 composites were successfully synthesized by ultrasonic mixing SG sheets and TiO2 spheres. SG–TiO2 composites exhibit high hydrogen production efficiency with a wide pH range (from pH = 3 to pH = 11). Under neutral pH (pH = 7), SG–TiO2-2 composite with the optimal amount of 2% SG sheets achieves the highest hydrogen evolution rate (ca. 260 μmol/h), which is more than 11 times higher than that of pure TiO2 and P25. The high hydrogen evolution rate can be owed to the promising properties of SG–TiO2 composites, including large surface area, efficient light absorption ability and high charge separation efficiency. More interestingly, SG–TiO2 composites can perform excellent hydrogen production activity under different pH conditions, even under alkaline condition, where the hydrogen production efficiency of GO–TiO2 composites usually decreased dramatically under such condition. This particular phenomenon can be attributed to the tight coordination between the SG sheets and TiO2 spheres, which prevents the damage of SG–TiO2 composites in the alkaline solution. Consequently, these novel SG–TiO2 composites can be widely applied in the practical clean energy production field.